Breast Carcinomatous Lymphangitis as an Unusual Presentation of Ovarian Cancer - Barbara Muoio (MDPI AG, 2021)
We describe the case of a 45-year-old woman with an unusual presentation of metastatic ovarian cancer. The patient presented to the oncological clinic with a three-week history of skin rash on the right breast. She underwent a chest and abdomen CT scan, which showed skin thickening of the right breast, right pleural effusion and bilateral cystic ovarian masses. Biopsy of a left ovarian lesion by diagnostic laparoscopy revealed the presence of ovarian serous carcinoma. Biopsy of the breast skin lesion revealed the presence of carcinomatous lymphangitis and immunohistochemistry documented the ovarian origin.